The effects of adherence to recommended antenatal services on adverse pregnancy outcomes in Northwest Ethiopia: multilevel and propensity score matching (PSM) modeling - Zelka, Muluwas Amentie; Yalew, Alemayehu Worku; Debelew, Gurmesa Tura (Frontiers in Global Women's Health, 2023)
Background: Adverse pregnancy outcomes are personal and social crises, caused by easily preventable pregnancy-related problems. Despite that, studies on the effectiveness of adherence to the continuity of ANC services were scarce. So, this study was used to determine the effectiveness of continuity of ANC services and determinants of adverse pregnancy outcomes. Methods: A prospective follow-up study design was conducted from March 2020 to January 2021 in Northwest Ethiopia among randomly selected study subjects. Data were collected by trained data collectors using pre-tested semi-structured questionnaires and analyzed using STATA Software version 14. A multilevel regression model was used to identify determinant factors, whereas the propensity score matching (PSM) model was used to look at the effectiveness of adherence to ANC services on adverse pregnancy outcomes. Results: Among 2,198 study participants, 26.8% had an adverse pregnancy outcome with 95%CI: 24.9 – 28.7 [abortion (6.1%; 95%CI: 5.1 – 7.1), LBW (11.5%; 95%CI: 10.2 – 12.9) and preterm (10.9; 95%CI: 9.6 – 12.3)]. Determinant factors were IFA supplementation (AOR=0.52), delay initiation of ANC visits at 4 – 6months (AOR = 0.5), after 6months (AOR = 0.2) and adhered to recommended ANC visits (AOR = 0.36), average time of PMRM 1 – 12 hours (AOR = 0.66) and pregnancy-related problems (AOR = 1.89). As treatment effect, adherence to continuity of visit-based ANC (β = - 0.11), content-based ANC services (β = - 0.04) and continuum of care via space dimension ANC (β = - 0.11) were statistically significant on reduction of adverse pregnancy outcome. Conclusion: In the study area, adverse pregnancy outcome was high. Even though adherence to the continuity of ANC services via time and space dimension were effective in the prevention of adverse pregnancy outcome, programmatically important factors were detected. Therefore, key strategies for promoting the uptake of antenatal services and strengthening IFA supplementation are strongly recommended.